Predictors of futile recanalization after endovascular therapy in anterior circulation stroke with large core infarction - Li, Qinhong; Ding, Chawen; Chen, Boyu; Tian, Zhenxuan; Chen, Yujie; Li, Linyu; Yu, Nizhen; Song, Jiaxing; Yang, Jie; Guo, Changwei; Huang, Jiacheng; Zi, Wenjie; et al. (Frontiers in Neurology, 2025)
BackgroundThere is a lack of data to predict futile recanalization (FR) after endovascular treatment (EVT) in acute anterior circulation large vessel occlusion (ACLVO) with large core infarction.MethodsThis analysis included patients from a national multicenter stroke registry (November 2021 to February 2023). Patients who achieved successful recanalization (expanded Thrombolysis in Cerebral Infarction [eTICI] score ≥2b) after EVT were categorized into two groups: meaningful recanalization (MR; 90-day modified Rankin scale [mRS] 0–3) and FR (mRS 4–6). Multivariate logistic regression was performed to identify independent predictors of FR.ResultsAmong 313 patients with successful recanalization, 171 (54.6%) experienced FR, and 142 (45.4%) achieved MR. Multivariate analysis showed that a higher baseline NIH Stroke Scale score (p < 0.001), older age (p < 0.001), elevated blood glucose (p = 0.003), poor collateral circulation (p = 0.004), and incomplete recanalization (eTICI 2b vs. 3; p < 0.001) were predictors of FR.ConclusionIn patients with ACLVO and large core infarction, age, hyperglycemia, baseline NIHSS, poor collaterals, and incomplete recanalization were independent predictors of FR. These findings may be used to guide treatment decisions and optimize management processes.